Buton Natural Rock Asphalt (BNRA) Modified Base Course Material - Rahmat Akbar Badaru; Randy Yudistira; Gatot Rusbintardjo; Faiqun Ni’am (International Conference on Coastal and Delta Areas, 2017)
In flexible pavement, base course is the layer immediately under the wearing surface layer. Because the base course lies close under the pavement surface, it is subject to severe loading. It follows the materials in a base course must be of extremely high quality. To get high quality of base course, research on treated base course with Buton Natural Rock Asphalt (BNRA) have been conducted. Amount of 10, 15, 20, 25, 30, and 35% BNRA by weight of base course aggregate are mixed in the base course aggregate. California Bearing Rasio (CBR) and direct shear test are performed to the mixed of BNRA-base course and also to the original base course to konw how far the influence of BNRA to improve the strength or quality of the base course. The test results show that with BNRA 25% the CBR value can increase from 52.30% to 98%, and cohesion change from 0.127 for original become 0.199 for base course treated BNRA, as well as angle of internal friction (φ) increase from 210 to 430. It can be concluded that BNRA is suitable to use as material for treated base. Keywords: Buton-Natural Rock Asphalt, Treated, Base Course, Improve, Strength.